(untitled) (New York, 1983)
This book brings together twenty-six classic and contemporary articles on the social and personality development of the child. Focusing on major events in the child's life, from infancy through adolescence, these multidisciplinary essays provide the essential statement on the central topics in the field: attachment, peer relations, play, identity crisis, and so on.
Keywords: Adolescent psychology,Hild development,Child psychology,Infant psychology; Addresses, essays, lectures,Addresses, essays, lectures,Addresses, essays, lectures